Legal Protection Of Residential Consumers - Asman Siagian; Rahmadany (International Journal of Society and Law, 2024)
The purpose of this study is to examine the legal safeguards available to homebuyers. During the process of buying and owning a house, housing customers frequently encounter complicated risks and concerns. For this reason, sufficient legal protection is necessary to safeguard the rights of consumers in real estate transactions.An examination of relevant legal documents and a review of the literature served as the research methodology for this project. Researchers gathered information about the legal protection of homebuyers from a range of legal sources, including statutes, rules, and court rulings. Subsequently, a qualitative analysis is conducted to pinpoint the advantages and disadvantages of the current legal safeguards.The findings of the study demonstrate that despite the existence of several laws and rules protecting housing customers legally, there are still issues and difficulties with their application. Several of the issues.